Hardware and Software: Verification and Testing 8th International Haifa Verification Conference, HVC 2012, Haifa, Israel, November 6-8, 2012. Revised Selected Papers - Biere, Armin; Nahir, Amir.; Vos, Tanja; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 8th International Haifa Verification Conference, HVC 2012, held in Haifa, Israel in November 2012. The 18 revised full papers presented together with 3 poster presentations were carefully reviewed and selected from 36 submissions. They focus on the future directions of testing and verification for hardware, software, and complex hybrid systems.
On Behavioral Programming -- Verifying Real-Time Software Is Not Reasonable: Abstract of Invited Talk -- SMT in Verification, Modeling, and Testing at Microsoft -- Reducing Costs While Increasing Quality -- Special Session on Security Verification -- Circuit Primitives for Monitoring Information Flow and Enabling Redundancy -- Formal Analysis of Security Data Paths in RTL Design -- Precise Detection of Atomicity Violations -- Proving Mutual Termination of Programs -- Knowledge Based Transactional Behavior -- Repair with On-The-Fly Program Analysis -- Computing Interpolants without Proofs -- MaxSAT-Based MCS Enumeration -- Automated Reencoding of Boolean Formulas.
Keywords: Computer science; Software engineering; Programming languages (Electronic computers).; Computer logic; Mathematical logic; Artificial intelligence; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Electronic books